ANALISIS EKONOMI KELUARGA PETANI KRATOM (Mitragyna Speciosa) DESA NANGA EMBALOH KECAMATAN EMBALOH HILIR KABUPATEN KAPUAS HULU - Supriadi, Irvan; Mashudi, Mashudi; Matsum, Junaidi H. (Universitas Tanjungpura, 2023)
This study aims to examine (1) the amount of income of kratom farmers (2) the economic situation of kratom farmer families (3) the strategy of kratom farmers in increasing income. This type of research is a case study, which aims to find out intensively, in detail and in depth about an event and business activity carried out by kratom farmers in meeting the economic needs of the family. The research data source is 5 kratom farmers. There are 3 types of data collection techniques, namely interviews, observation, and documentation. Data collection tools are interview guides, in-depth interviews and Focus Group Discussion (FGD). The results of the study (1) Kratom Farmers' income ranges from Rp. 9,220,000.- up to Rp. 11,700,000, - the highest income in informant 4 and informant 5 is Rp. 11,700,000, - Then followed by Informant 2 of Rp. 11,530,000, - then Informant 1 of Rp. 10.90.000, - and lastly the smallest income of informant 3 is Rp. 9,220,000.- per month. (2) The 5 kratom farmers use the income from their kratom business for food needs and children's snacks, education costs, health costs, to build/rehab houses, after all these costs are met they set aside savings/savings every month, where informant 1 saves Rp. 3,890,000, - informant 2 saved Rp. 3,890,000, - informants 3 Rp. 4,220,000, - informant 4 saved Rp. 5,000,000, - and the last informant 5 Rp. 5.200.000,-. (3) Strategies carried out by kratom farmers by maintaining the quality of kratom crops, carrying out kratom production processes to the maximum, carrying out optimal kratom processing, establishing cooperation, optimizing kratom land to the maximum, carrying out periodic maintenance, developing new kratom planting areas and minimizing as well as cutting costs incurred in the kratom farming business.